2018
DOI: 10.1021/acs.jpcc.8b09998
|View full text |Cite
|
Sign up to set email alerts
|

Deswelling Dynamics of Thermoresponsive Microgel Capsules and Their Ultrasensitive Sensing Applications: A Mesoscopic Simulation Study

Abstract: Thermoresponsive microgels with a hollow capsule architecture have been widely used in drug delivery and molecular encapsulation, and their efficacy is contingent on the internal structure in the deswelling dynamics process. Despite a large number of experimental studies on microgels, proper theoretical methods based on an individual microgel capsule are still a few because of the complexity of the microgels. Herein, we first propose a novel methodology to investigate the structural properties and deswelling d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 68 publications
5
35
0
1
Order By: Relevance
“…Herein, we focus on the tetrafunctional crosslinker, which crosslinks four polymer chains, and it is modeled as a single particle. The nanohydrogel structure is constructed by a similar method as reported by Richtering et al ; it also can be found in our previous studies. , Through repeating an ideal diamond cubic crystal structure, the fully stretched linear chains with equal lengths are connected by a tetrafunctional crosslinker, and then, it can be tailored into the targeted geometry. Some literature has demonstrated that this model can describe the general structure–property relations of temperature-dependent swelling dynamics and surface pressure of microgels. ,, Owing to the crystalline order effects, it was found that this model just can compare the form factor with a fuzzy sphere model at small wave vectors rather than at intermediate scales. , Herein, we focus on swelling nanohydrogels under good solvent conditions, whose diameters are lower than 30 nm (see Table S1).…”
Section: Computational Methods and Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we focus on the tetrafunctional crosslinker, which crosslinks four polymer chains, and it is modeled as a single particle. The nanohydrogel structure is constructed by a similar method as reported by Richtering et al ; it also can be found in our previous studies. , Through repeating an ideal diamond cubic crystal structure, the fully stretched linear chains with equal lengths are connected by a tetrafunctional crosslinker, and then, it can be tailored into the targeted geometry. Some literature has demonstrated that this model can describe the general structure–property relations of temperature-dependent swelling dynamics and surface pressure of microgels. ,, Owing to the crystalline order effects, it was found that this model just can compare the form factor with a fuzzy sphere model at small wave vectors rather than at intermediate scales. , Herein, we focus on swelling nanohydrogels under good solvent conditions, whose diameters are lower than 30 nm (see Table S1).…”
Section: Computational Methods and Simulation Detailsmentioning
confidence: 99%
“…The nanohydrogel structure is constructed by a similar method as reported by Richtering et al; 57 it also can be found in our previous studies. 58,59 Through repeating an ideal diamond cubic crystal structure, the fully stretched linear chains with equal lengths are connected by a tetrafunctional crosslinker, and then, it can be tailored into the targeted geometry. Some literature has demonstrated that this model can describe the general structure−property relations of temperature-dependent swelling dynamics and surface pressure of microgels.…”
Section: Computational Methods and Simulation Detailsmentioning
confidence: 99%
“…[35][36][37] This result is reproduced in a fairly wide range of interaction parameters as well as the flexibility of the subchains. 38,39 However, following such strategy one could notice, that simulation of the hollow ellipsoidal microgels failed and could not reproduce the experimental observations. 34 In particular, different trends of the shape/size evolution of the shell and the void upon collapse above their volume phase transition temperature (VPTT) are observed or extra flattening of the microgel at the interfaces is detected.…”
Section: Computer Simulationsmentioning
confidence: 99%
“…Stimuli-responsive hollow particles, especially hollow micro-sized or nano-sized spheres, continue to attract major interest because they have wide potential applications in fields such as dye precipitation [1], catalysis [2,3], sensors [4][5][6], and especially controlled delivery systems [7][8][9][10]. Early studies on hollow polymeric microspheres were conducted by Caruso et al [11].…”
Section: Introductionmentioning
confidence: 99%